PENILAIAN KINERJA MELALUI WORK PERFORMANCE KARYAWAN PT. KONIMEX PHARMACEUTICAL LABORATORIES - Richo Riawan; Djumali Djumali; Ida Aryati (JURNAL ILMIAH EDUNOMIKA, 2020)
This study used a quantitative approach. Respondents were employees of PT Konimex Pharmaceutical Laboratories. Technique sampling were used at this study was accidental sampling. The number of samples obtained was 175 respondents. Data analysis techniques using the PAWS Statistics Program 18. Hypothesis testing used Multiple Linear Regression Test which includes t test, F test, and the coefficient of determination. The results showed that: (1) functional structure had a significant effect on employee work performance; (2) incentive policies significantly influence employee work performance; (3) work culture has a significant effect on employee work performance; (4) functional structure, incentive policy, and work culture simultaneously affect the work performance of employees of PT Konimex Pharmacutical Laboratories. Keywords: Functional Structure, Incentive Policy, Work Culture, Work Performance